Space Flight Effects on Antioxidant Molecules in Dry Tardigrades: The TARDIKISS Experiment. (13th January 2015) - Rizzo, Angela Maria; Altiero, Tiziana; Corsetto, Paola Antonia; Montorfano, Gigliola; Guidetti, Roberto; Rebecchi, Lorena
Abstract : The TARDIKISS (Tardigrades in Space) experiment was part of the Biokon in Space (BIOKIS) payload, a set of multidisciplinary experiments performed during the DAMA (Dark Matter) mission organized by Italian Space Agency and Italian Air Force in 2011. This mission supported the execution of experiments in short duration (16 days) taking the advantage of the microgravity environment on board of the Space Shuttle Endeavour (its last mission STS-134) docked to the International Space Station. TARDIKISS was composed of three sample sets: one flight sample and two ground control samples. These samples provided the biological material used to test as space stressors, including microgravity, affected animal survivability, life cycle, DNA integrity, and pathways of molecules working as antioxidants. In this paper we compared the molecular pathways of some antioxidant molecules, thiobarbituric acid reactive substances, and fatty acid composition between flight and control samples in two tardigrade species, namely, Paramacrobiotus richtersi and Ramazzottius oberhaeuseri . In both species, the activities of ROS scavenging enzymes, the total content of glutathione, and the fatty acids composition between flight and control samples showed few significant differences. TARDIKISS experiment, together with a previous space experiment (TARSE), further confirms that both desiccated and hydrated tardigrades represent useful animal tool for space research.